MATHEMATICAL MODEL OF GRAIN RAW MOVEMENT IN INTERACTIONWITH DISPERSER AND SCREW FEEDER - NAUMENKO, MYKOLA; МYKOLENKO, SVETLANA; GURIDOVA, VICTORIA; HEZ, YANA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Bioactivated dispersed grain, which is obtained by soaking followed by grinding on a dispersant is a promising raw material for expanding the range of bakery products and providing the population with products of high biological value. Bioactivation is understood as the process of grain saturation with moisture, during which the transformation of macromolecular substances into easily accessible forms takes place, which makes it a source of bioactive substances. However, the implementation of the process of dispersing bioactivated grain material remains relevant, the process of grinding which is mainly influenced by such factors as moving the grain with the help of a screw feeder and pushing it through the cutting mechanism.To obtain dispersed grain, there are a large number of crushing machines, the main working bodies of which are the screw feeder, knives and lattice. Many scientific papers are devoted to improving the helical transport mechanism of the disperser, by changing its design, which allows to increase the homogeneity of the grain mass at the outlet, its dispersion, reduce energy consumption and increase productivity. However, the use of screw feeders for grain dispersion raises a number of issues that require further research. Namely, the study of the influence of the additional pressure required to work when loading the material on the process of its movement, and determining the speed of movement of the grain material through the cutting mechanism for grinding in the dispersant.To address the above issues, a mathematical model for the movement of grain raw materials during grinding is proposed. Mathematical dependences for determining the speed of the dispersing process have been obtained, which can be applied taking into account the physical properties of the material in the stationary mode of operation of the dispersant.
Keywords: dispersant; grain bioactivation; auger; grain mixture; stationary mode; algebraic parameters; kinematic characteristics